Handbook of LAN technology - Fortier, Paul J. (McGraw-Hill series on computer communications, 1992)
Reflecting changes in local area network environments, this 2nd edition covers topics such as LANS and industry users, digital communications technology and error management, topology considerations, control and standards issues, security, software and applications and systems management.